Designing irregular verb game as teaching tool for learning irregular verbs - Ari Rifaldi; Bilal Qureshi; Eni Rosnija (UPT Bahasa Universitas Tanjungpura, 2022)
This research aimed to validate the authenticity and usefulness of Irregular Verb Game as a teaching tool in learning past tense irregular verbs in English language class. This research involved an English teacher and students of grade eight at SMPN 3 Salatiga, Kabupaten Sambas. The research method was development which consists of three phases: analyzing, designing, and developing. For the analysis phase, the researcher used interview sheets to obtain the data that highlights teacher and students’ needs in teaching and learning. The design phase focused on designing the contents and layout of the product. The development phase generated the product, tried it out, and got teacher’s validation by using assessment rubric. The first part of the result of this research was a complete design of the product. The layout of the design had 3 main parts: intro, inside house, and outside house. The contents included a visual dictionary, pronunciation function, and simple quizzes. The second part of the result was the teacher’s validation for the product. The percentage of teachers’ validation for the product’s effectiveness was 94.44%. Based on this data, the researchers ensured that Irregular Verb Game can be used as a teaching tool to teach irregular verbs in the form of past tense for eighth grade students of Junior High School.